2021
DOI: 10.1155/2021/3839235
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Antibacterial Properties of a 3D Flower-Like TiO2 Nanostructure Photocatalyst

Abstract: Flower-like titanium dioxide (TiO2) nanostructures are successfully synthesized using a hybrid sol-gel and a simple hydrothermal method. The sample was characterized using various techniques to study their physicochemical properties and was tested as a photocatalyst for methyl orange degradation and as an antibacterial material. Raman spectrum and X-ray diffraction (XRD) pattern show that the phase structure of the synthesized TiO2 is anatase with 80-100 nm in diameter and 150–200 nm in length of flower-like n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The Ag@TiO 2 NRs was successfully synthesised in this study because all peaks belonging to the Ag FCC structure were observed at 38.02°, 44.40°, 64.70°, and 77.72°, as well as other peaks at 25.62°, 38.28°, 48.16°, 53.9°, 54.34°, 55.36°, 63.06°, and 69.26°that can be indexed to (101), (004), ( 200), ( 105), ( 211), (204), and (220) tetragonal crystal planes of anatase TiO 2 (figure 3) (b). As reported by other researchers, a prominent peak at ∼25°is exclusive to the anatase TiO 2 (101) crystallographic plane [37,38]. The presence of sharp peaks was attributed to the crystalline structure of the Ag@TiO 2 NRs sample.…”
Section: Resultssupporting
confidence: 75%
“…The Ag@TiO 2 NRs was successfully synthesised in this study because all peaks belonging to the Ag FCC structure were observed at 38.02°, 44.40°, 64.70°, and 77.72°, as well as other peaks at 25.62°, 38.28°, 48.16°, 53.9°, 54.34°, 55.36°, 63.06°, and 69.26°that can be indexed to (101), (004), ( 200), ( 105), ( 211), (204), and (220) tetragonal crystal planes of anatase TiO 2 (figure 3) (b). As reported by other researchers, a prominent peak at ∼25°is exclusive to the anatase TiO 2 (101) crystallographic plane [37,38]. The presence of sharp peaks was attributed to the crystalline structure of the Ag@TiO 2 NRs sample.…”
Section: Resultssupporting
confidence: 75%
“…With the increasing industrialization and urbanization, the limitation of the fresh waterbodies and elevating water pollution can be the critical recognized issue. The 3D-flower like composites acts as a photocatalyst for photocatalytic degradation of the certain organic pollutant such as a pesticide, dyes, antibacterial material and drugs can be done using efficient visible light irradiation [41][42][43][44][45][46][47][48][49]. In photocatalytic applications of 3D flower-like composites, BiOCl-containing 3D composites were discovered to have enhanced visible light sensitivity because BiOCl had less activity in visible light.…”
Section: Introductionmentioning
confidence: 99%
“…This class of materials possesses the general formula of ABX 3 where A is a cation (organic/inorganic), B is a divalent metal (Pb 2+ , Sn 2+ , Ge 2+ ), and X is an anion (Cl 1- , Br 1- , I 1- or mixture) ( Kulkarni et al, 2019 ; Yang et al, 2019 ). In recent years, semiconductor materials have been widely used as photocatalyst in the environmental and energy sectors due to their novel physiochemical features and cost-effectiveness ( Batool et al, 2020 ; Shen et al, 2021b ) Commonly used metal-based semiconducting photocatalysts include TiO 2 ( Fujishima et al, 2000 ) ( Zhang et al, 2021b ), Fe 2 O 3 ( Hitam and Jalil, 2020 ), CdS ( Cheng et al, 2018 ), MoS 2 ( Shen et al, 2020 ), ZnS ( Lee and Wu, 2017 ), and ZnO ( Johar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%